ANALISIS PENGATURAN PERTANGGUNGJAWABAN PEMERINTAH DAERAH KABUPATEN KARWANG TERHADAP ANAK TERLANTAR BERDASARKAN PERATURAN DAERAH NO. 8 TAHUN 2012 TENTANG PENYELENGGARAAN KESEJAHTERAAN SOSIAL - Resta Safira; Margo Hadi Pura (JURNAL ILMIAH LIVING LAW, 2022)
In Indonesia, it seems that not every legal protection policy for displaced children applied so far is based on a deep understanding of the problem. The policy of legal protection of displaced children applied so far tends to be patchy only, if not to be said contradictions. This is because the law that is supposed to protect the basic rights of displaced children is actually struggling with its own problems this social problem that plagues the city of Karawang is becoming a duty and responsibility to displaced children This research method is used normative juridical that focuses on the facts in a society and the main data obtained through observation and interview and by conducting a decscriptive approach of legal interpretation, namely the study of libraries or documents while in addition to juridical has been regulated in its implementation there are still obstacles or obstacles and some steps taken by the district government of Karawang, namely Din as Social is an important key to solving this problems.